Expected Net Benefit of Vaccinating Rangeland Sheep against Bluetongue Virus Using a Modified-Live versus Killed Virus Vaccine - Munsick, Tristram R.; Peck, Dannele E.; Ritten, John P.; Jones, Randall; Jones, Michelle; Miller, Myrna M. (Frontiers in Veterinary Science, 2017)
Recurring outbreaks of bluetongue virus in domestic sheep of the U.S. Intermountain West have prompted questions about the economic benefits and costs of vaccinating individual flocks against bluetongue disease. We estimate the cost of a bluetongue outbreak on a representative rangeland sheep operation in the Big Horn Basin of the state of Wyoming using enterprise budgets and stochastic simulation. The latter accounts for variability in disease severity and lamb price, as well as uncertainty about when an outbreak will occur. We then estimate the cost of purchasing and administering a bluetongue vaccine. Finally, we calculate expected annual net benefit of vaccinating under various outbreak intervals. Expected annual net benefit is calculated for both a killed virus vaccine and modified-live virus vaccine, using an observed price of 0.32 per dose for modified-live, and an estimated price of 1.20 per dose for killed-virus. The modified-live vaccine’s expected annual net benefit has a 100% chance of being positive for an outbreak interval of 5, 10, or 20 years, and a 77% chance of being positive for a 50-year interval. The killed virus vaccine’s expected annual net benefit has a 97% chance of being positive for a 5-year outbreak interval, and a 42% chance of being positive for a 10-year interval. A killed virus vaccine is therefore unlikely to be economically attractive to producers in areas exposed less frequently to bluetongue disease. A modified-live vaccine, however, requires rigorous authorization before legal use can occur in Wyoming. To date, no company has requested to manufacture a modified-live vaccine for commercial use in Wyoming. The killed virus vaccine poses less risk to sheep reproduction and less risk of unintentional spread, both of which facilitate approval for commercial production. Yet our results show an economically consequential tradeoff between a killed virus vaccine’s relative safety and higher cost. Unless the purchase price is reduced below our assumed 1.20 per dose, producer adoption of a killed virus vaccine for bluetongue is likely to be low in the study area. This tradeoff between cost and safety should be considered when policymakers regulate commercial use of the two vaccine types.